STRATEGI PEMBELAJARAN MELALUI MAGANG PROGRAM MERDEKA BELAJAR KAMPUS MERDEKA PADA PROGRAM STUDI PERBANKAN SYARIAH DI ERA PANDEMI - Rahmawati, Rafika; Adham, Adham (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2023)
The development of Islamic banking in Indonesia increases the need for competent practitioners from Islamic Banking Study Program graduates. These graduates can reduce the need for basic training, thereby increasing the efficiency of Islamic banks. The government supports this through policies such as the Indonesian National Qualifications Framework (KKNI) and Merdeka Belajar Kampus Merdeka (MBKM), which aim to create a link and match between higher education and industry. Internships are a form of MBKM learning that can strengthen student competencies. The Analytic Network Process (ANP) method identifies and analyzes problems supporting MBKM in the Islamic Banking Study Program. The research shows two main issues: the duration of internships that the industry considers too long and the difficulty of ensuring learning outcomes (LLOs) by academics. The recommended strategies to overcome these problems include: Establishing good relationships with partners, Improving systems and procedures, Conducting partner selection, Increasing the number of partners. Implementing these strategies is expected to improve the effectiveness and efficiency of the learning process through internships.